Netralitas Pegawai Negeri Sipil Dari Pengaruh Politik Terhadap Birokrasi Pemerintahan Indonesia - Diana, Bambang; Sigiro, Benny Sigiro (Bahasa Indonesia, 2025)
ASN is an employee who is appointed by the official responsible for employees. They receive salaries and benefits from the state. Bureaucratic neutrality means that the bureaucracy does not favor the interests of certain groups or groups, especially those with power. The purpose of this paper is to explain the neutrality of ASN. The bureaucracy should be separate from certain groups and needs to see itself as adifferent social group, which does not become a tool for the dominant group or ruler. In this writing,the literacy method is used, where the results of the writing are taken from documents, books, and news written, and analyzed in the existing reviews. The bureaucracy is in charge of implementing political policies, so it must not be involved with the political interests of any group